Active and healthy ageing in urban environments: laying the groundwork for solution-building through citizen science. (14th September 2022) - Wood, Grace E R; Pykett, Jessica; Stathi, Afroditi
Summary: Urban age-friendly initiatives strive to promote active and healthy ageing by addressing urban influences that impact individuals as they age. Collaborative community partnerships with multi-level stakeholders are crucial for fostering age-friendly initiatives that can transform urban community health. Employing a citizen social science (CSS) approach, this study aimed to engage older adults and stakeholders in Birmingham, UK, to (i) identify key urban barriers and facilitators to active and healthy ageing, and (ii) facilitate collaboration and knowledge production to lay the groundwork for a citizen science project. Older adults ( n = 16; mean age = 72(7.5 SD); 11 female) and community stakeholders ( n = 11; 7 female) were engaged in six online group discussions, with audio recordings transcribed and thematically analysed to present key urban barrier and facilitator themes. Ageism, winter, technology and safety were barriers identified by both groups. Outdoor spaces and infrastructure, transportation, community facilities, and Covid-19 pandemic were identified as barriers and/or facilitators. Older adults identified the ageing process as a barrier and diversity of the city, health and mobility and technology as facilitators. For stakeholders, barriers were deprivation and poverty, gender differences, and ethnicity, whereas age-inclusive activities were a facilitator. Organic and active opportunities for older adults and stakeholders to connect, co-produce knowledge on urban environments and share resources presented foundations of solution-building and future collaboration. CSS effectively facilitated a range of stakeholders across local urban spaces to collaborate and co-produce ideas and solutions for enhancing local urban environments to promote active and healthy ageing. Lay Summary: Planning urban age-friendly environments requires engagement with local residents, service providers and decision-makers. This is important for developing joint actions, urban initiatives and allowing these individuals to share their experiences, needs and resources. Citizen social science (CSS) can engage residents and stakeholders to directly shape social research aiming to improve urban environments. This study engaged 16 older adults over the age of 60 and 11 stakeholders to identify urban features that influence active and healthy ageing in Birmingham, UK. Using six online discussion groups, the key urban barriers and facilitators were identified by older adults and stakeholders, who also checked the findings to confirm they represent the discussions accurately. Urban barriers and facilitators included health and mobility, ageism, outdoor spaces and infrastructure, transportation, technology, Covid-19, and the lack or presence of community facilities and activities. During discussion groups, both older adults and stakeholders connected to share information about local organizations, resources, websites for free activities or research, and provide solutions for each other's barriers. CSS effectively engaged older adults and stakeholders to collaborate and create knowledge together for improving local urban environments in Birmingham.